2018
DOI: 10.1002/bit.26570
|View full text |Cite
|
Sign up to set email alerts
|

RNAi assisted genome evolution unveils yeast mutants with improved xylose utilization

Abstract: Xylose is a major component of lignocellulosic biomass, one of the most abundant feedstocks for biofuel production. Therefore, efficient and rapid conversion of xylose to ethanol is crucial in the viability of lignocellulosic biofuel plants. In this study, RNAi Assisted Genome Evolution (RAGE) was used to improve the xylose utilization rate in SR8, one of the most efficient publicly available xylose utilizing Saccharomyces cerevisiae strains. To identify gene targets for further improvement, we created a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
(92 reference statements)
0
23
0
Order By: Relevance
“…Overexpression of genes such as MDH1 (mitochondrial malate dehydrogenase), VPS13 (involved in vacuolar protein sorting, mitochondrial integrity and protein‐Golgi retention), and COX5a (Subunit Va of cytochrome c oxidase) were found to be increase xylose assimilation and ethanol productivity. RNAi assisted downregulation of endogenous genes were also employed, which identified downregulation of CDC11 to be beneficial …”
Section: Engineering Xylose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of genes such as MDH1 (mitochondrial malate dehydrogenase), VPS13 (involved in vacuolar protein sorting, mitochondrial integrity and protein‐Golgi retention), and COX5a (Subunit Va of cytochrome c oxidase) were found to be increase xylose assimilation and ethanol productivity. RNAi assisted downregulation of endogenous genes were also employed, which identified downregulation of CDC11 to be beneficial …”
Section: Engineering Xylose Metabolismmentioning
confidence: 99%
“…While initial engineering attempts identified flux limitations in xylose isomerase and PPP shunt, further directed evolution and metabolic engineering have iteratively removed rate limitations in several of these metabolic reactions. Adaptive laboratory evolution (ALE) studies on extensively engineered strains have been identifying mutations in proteins that are involved in regulation, signaling, etc., insinuating the need to look at limitations beyond metabolic fluxes . Similarly, mutations or variations in expression of signaling pathway genes or regulatory genes have been shown to further increase growth rates in galactose…”
Section: Comparing Native and Non‐native Sugar Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, gene overexpression was achieved when cDNA molecules were transcribed in the sense direction, whereas gene repression was achieved through transcription of antisense RNAs in the presence of a heterologous RNAi pathway. Using this collection of modulation parts, both gene overexpression and knockdown targets were successfully identified in laboratory and industrial yeast strains for improved cellulase expression, isobutanol production, and xylose utilization ( Si et al, 2017 ; HamediRad et al, 2018 ). Notably, in addition to isolating individual mutant strains, genome-wide mapping of gene–trait relations can be also achieved.…”
Section: Applicationmentioning
confidence: 99%
“…These studies demonstrated several unique advantages. First, unlike gene deletion collections that are available only in certain laboratory strains ( Scherens and Goffeau, 2004 ), genome-wide RNAi libraries can be readily introduced in a custom strain background, such as CEN.PK ( Si et al, 2014 , 2017 ; Wang et al, 2019 ), BY4741 ( Xiao and Zhao, 2014 ; Crook et al, 2016 ; Lee et al, 2016 ), and industrial strains ( Si et al, 2017 ; HamediRad et al, 2018 ). Notably, this feature enables the use of directed evolution strategies in genome-wide engineering, whereby beneficial mutations can be continuously accumulated in an evolving yeast genome ( Si et al, 2014 ).…”
Section: Applicationmentioning
confidence: 99%